Validation with videometry of an integrated system to assess horizontal intra-cyclic velocity with a mechanical speed-meter - Barbosa, T. M.; Costa, M. J.; Morais, J. E.; Jesus, S.; Silva, A.; Batista, J.; Goncalves, J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this paper was to: validate an integrated system (i.e., software application and hardware after calibration) to assess humans horizontal intra-cyclic velocity with a mechanical speedo-meter. System validation was done for a set of land-based human locomotion techniques (from slow walk to maximal running) in four subjects and comparing it with a videometric system (i.e. APAS). There were no significant differences between pair wise data (speedo-meter versus APAS data) using students t-test for both velocity coefficient of variation and maximal velocity. Linear regression models were very high for both the velocity coefficient of variation and maximal velocity. More than 80% of the Bland-Altman plots were within 1.96 standard-deviations.